(untitled) (Revista Apotheke, 2025)
This article aims to analyze some works within the hybrid productions by the multi-talented visual artist and poet Nuno Ramos. To achieve this, it employs a historical overview of the transformations in modern and contemporary art, alongside a theoretical-critical framework regarding the unspecific forms of the literary, based on the studies of Florencia Garramuño. The central proposal of this text is to investigate the extent to which the conjunction of distinct materials constitutes a unique hallmark and signature of Nuno Ramos, an aspect that also resonates sharply in his verbal production. Indeed, through exhibitions, installations, literary works, and interviews, it is concluded that the inventiveness and fabulation exercised in the artist’s words and visualities stand as the central distinguishing feature of his work in contemporary times.